The heritage education and the incentive practices to local cultures (Simbiótica. Revista Eletrônica, 2016)
From an analytical-reflexive perspective, this article aims to think about the contribution of Patrimonial Education in the development of local cultures, analyzing their practices through projects and programs in Brazil’s many different regions that through memory, tangible and intangible heritage of cities and states contribute to the strengthening of local identities and the pursuit of a more effective citizenship.Keywords: education; patrimony; culture; practices.